Blockchain technology in the hospitality sector: Exploring opportunities and challenges in Bangladeshi hotels - Hossan, Farooq; Islam, Md. Touhidul; Hasan, Mohammad Kamrul (Journal of Asian Business Strategy, 2025)
Blockchain technology creates a good opportunity with different challenges that can be applied in the hospitality industry. The vital question is how blockchain technology can be effectively integrated into Bangladeshi hotel operations to enhance efficiency, security, and customer satisfaction while addressing adoption challenges and opportunities. While previous research highlights blockchain’s potential to transform hospitality operations, most studies are conceptual or focused on developed nations, revealing a need for empirical research that addresses the unique challenges and opportunities in Bangladeshi hotel operations. This study employs a qualitative approach, utilizing secondary data from literature and industry reports, along with expert interviews, and applies thematic analysis to explore blockchain adoption in Bangladeshi hotels. This study reveals that blockchain technology adoption in Bangladesh’s hospitality sector is at a nascent stage, primarily due to low awareness, infrastructural deficiencies, high costs, and a lack of skilled personnel, despite its recognized potential to enhance data security, operational efficiency, transparency, and guest experiences. The findings underscore the urgent need for strategic interventions such as capacity building, regulatory support, and pilot projects to bridge the technological gap, highlighting blockchain's transformative significance for achieving smarter, more resilient hotel operations in Bangladesh, aligned with national development goals like Vision 2041 and the growing demand for digital innovation in tourism.